Clinical spectrum and outcomes of fungal sepsis in neonates in the two neonatal intensive care unit of Bangladesh: a prospective observational study - Mannan, M. Abdul; Ferdousi, Farhana; Islam, M. Naeem; Nasrin, Ummey Tamima; Siddika, Ayesha; Rahman, Tareq; Hossain, M. Ismail; Alam, Mohammad Shakhawat (International Journal of Contemporary Pediatrics, 2024)
Background: Fungal infections have emerged as a significant cause of late-onset neonatal sepsis in the last two decades. Epidemiological data on fungal sepsis in neonates especially in the Bangladesh population is scarce. Fungal infections are frequent and major causes of septicemia in neonatal intensive care units and are associated with high morbidity and mortality. Objective of the study: This study aims to determine the epidemiological trend of neonatal fungal infection, the organisms, and their susceptibility pattern to the different antifungal agents and additionally to look for the various risk factors, clinical features, and laboratory manifestation of fungal sepsis in neonates. Method: This Prospective observational study was carried in Neonatal Intensive Care Unit (NICU) of Bangabandhu Sheikh Mujib Medical University (BSMMU) & Neonatal Intensive Care Unit (NICU) of Central hospital, Dhaka after approval from IRB. A total of 106 admitted neonates during the study period who were eligible for this study were included. On the basis of exclusion criteria 12 neonates were excluded. Blood culture was tested in the department of Microbiology of participating institutes. Results: After meeting all inclusion criteria 94 patients were included in the study. Most of the neonates (62.8%) were male and 67% were outborn. Around 34% Birth weight was between 2500gm to 3999gm followed by 31.9% in between 1000 gm to 1499 gm. Preterm were 69.2% and delivery by LUCS was 75.5%. Death occurred in 12.8% cases. Fungal growth were isolated in 69.1% cases. All were Candida species. There was no statically significant difference in between Culture positive and no growth group in terms of risk factors and laboratory findings except temperature instability. In culture positive group 82.4% cases had temperature instability compared to no growth group. All Candida species were sensitive to most of the antifungal agents except Candida ciferrii which was only sensitive to flucytosine. Conclusion: Candida is the most prevalent fungus in NICU. Candida ciferrii is an emerging fungus which is resistant to classical antifungal agents.